math

posted by .

solve for y?

z=0.3(y-6)^2

please can you explain your working,

Many thanks,

Wendy.

* Algebra - drwls, Friday, November 20, 2009 at 9:40am

(10/3)z = (y-6)^2
y = sqrt[(10/3)z] +6
= 1.826 sqrt z + 6

* Algebra - wendy, Friday, November 20, 2009 at 9:47am

I'm sorry. Really don't understand this. Where did the 10/3 come from in the first step?

  • math -

    .3 is 3/10
    if you move that across the equal sign, you get
    z=3/10 sqrt( )
    10/3 z= sqrt ( )
    then square both sides
    (10/3 z)^2=y-6
    y= (10/3 z)^2+6

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Inequality

    When I solve the inquality 2x^2 - 6 < 0, I get x < + or - sqrt(3) So how do I write the solution?
  2. Math(Roots)

    sqrt(24) *I don't really get this stuff.Can somebody please help me?
  3. math,algebra,help

    Directions are simplify by combining like terms. x radiacal 18 -3 radical 8x^2 can someone show me how to do these types of problems. thanks I cant determine the second term. For the first, I think you meant x sqrt(18) which reduces …
  4. Math

    How do you find a square root of a number that's not a perfect square?
  5. Math Help please!!

    Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine …
  6. Calculus

    Please look at my work below: Solve the initial-value problem. y'' + 4y' + 6y = 0 , y(0) = 2 , y'(0) = 4 r^2+4r+6=0, r=(16 +/- Sqrt(4^2-4(1)(6)))/2(1) r=(16 +/- Sqrt(-8)) r=8 +/- Sqrt(2)*i, alpha=8, Beta=Sqrt(2) y(0)=2, e^(8*0)*(c1*cos(0)+c2*sin(0))=c2=2 …
  7. Math/Calculus

    Solve the initial-value problem. Am I using the wrong value for beta here, 2sqrt(2) or am I making a mistake somewhere else?
  8. Algebra

    I have a question if someone could help, please explain it. Given b = -1 and h = -1, what is the equation of the graph if the parent function is y = sqrt (x) Answers: a.y = sqrt(x-1) b.y = sqrt (-x+1) c.y = - sqrt (-x-1) d.y = sqrt(-x-1) …
  9. Algebra-drwls please check!

    Posted by Megan on Tuesday, October 12, 2010 at 3:44pm. I have a question if someone could help, please explain it. Given b = -1 and h = -1, what is the equation of the graph if the parent function is y = sqrt (x) Answers: a.y = sqrt(x-1) …
  10. Algebra

    Evaluate sqrt7x (sqrt x-7 sqrt7) Show your work. sqrt(7)*sqrt(x)-sqrt(7)*7*sqrt(7) sqrt(7*x)-7*sqrt(7*7) sqrt(7x)-7*sqrt(7^2) x*sqrt 7x-49*x ^^^ would this be my final answer?

More Similar Questions